2021
DOI: 10.1155/2021/5585238
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Behavior Detection Framework Using HTM-Based Semantic Folding Technique

Abstract: Upon the working principles of the human neocortex, the Hierarchical Temporal Memory model has been developed which is a proposed theoretical framework for sequence learning. Both categorical and numerical types of data are handled by HTM. Semantic Folding Theory (SFT) is based on HTM to represent a data stream for processing in the form of sparse distributed representation (SDR). For natural language perception and production, SFT delivers a solid structural background for semantic evidence description to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Where context is the semantic granularity of the processing and determines the ability to generate semantic associations of encodings, context can be composed of a varying number of sentences. Khan et al [11] utilized SFT to encode Internet text and employed HTM models for online anomaly detection. Within the scope of our research, we observed that only Webber et al [10] constructed a semantic grid and effectively applied its encoding in commercial applications of natural language processing.…”
Section: Related Workmentioning
confidence: 99%
“…Where context is the semantic granularity of the processing and determines the ability to generate semantic associations of encodings, context can be composed of a varying number of sentences. Khan et al [11] utilized SFT to encode Internet text and employed HTM models for online anomaly detection. Within the scope of our research, we observed that only Webber et al [10] constructed a semantic grid and effectively applied its encoding in commercial applications of natural language processing.…”
Section: Related Workmentioning
confidence: 99%
“…In the training phase, the model is typically accurate, but in the testing phase, the model's performance declines. As a result, in order to overcome the model's performance error in terms of underfitting and overfitting, the validation set must be used [22]. Keras has two methods for determining the optimum model parameters: manual data validation and automatic data validation [3].…”
Section: Validation Setmentioning
confidence: 99%